2023
DOI: 10.3390/lubricants11010017
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Approach in the Simulation of the Robustness Boundaries of Tribosystems under the Conditions of Boundary Lubrication

Abstract: In the presented work, a methodical approach was developed for determining rational operation modes of tribosystems, taking into account their design. This approach makes it possible in the designing stage, according to the predicted operating modes, to calculate the limits and margins of stable work in operation. The definition of the robustness of the tribosystem and the criteria for assessing the robustness are formulated based on the theory of stability of technical systems. It is shown that such a methodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…From the review of the works given in the review of literary sources, it can be concluded that the most promising program or mode of running-in of tribosystems is running-in "on the edge of burr", in our case "on the edge of loss of stability of the tribosystem". From the conclusions of the work [19] it follows that the loss of stability of the tribosystem, depending on the magnitude of the load and speed of sliding and the speed of external influence, may occur in the form of the appearance of accelerated wear or burr. Therefore, the term "on the verge of loss of stability of the tribosystem" is more correct.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the review of the works given in the review of literary sources, it can be concluded that the most promising program or mode of running-in of tribosystems is running-in "on the edge of burr", in our case "on the edge of loss of stability of the tribosystem". From the conclusions of the work [19] it follows that the loss of stability of the tribosystem, depending on the magnitude of the load and speed of sliding and the speed of external influence, may occur in the form of the appearance of accelerated wear or burr. Therefore, the term "on the verge of loss of stability of the tribosystem" is more correct.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of running-in modes is determined by the limit of loss of stability of the tribosystem, the method of determining which is given in [19]. During running-in, the process of converting the mechanical energy of friction into internal energy, primarily thermal energy, which is dissipated into the environment due to thermal conductivity, as well as the energy of structural changes in the surface layers of triboelement materials, takes place.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations